1980
DOI: 10.1179/pom.1980.23.3.113
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Phase Sintering of Al—Cu Compacts

Abstract: The sintering of AI-Cu compacts made from powder mixtures has been studied by dilatometry and metallography in an attempt to elucidate the mechanism of dimensional changes occurring in this alloy system. Sintering kinetics are governed by the formation and spreading of eutectic liquid; this has been found to be influenced by the formation of intermetallic phases during heating to,.the eutectic temperature.Liquid phase sintering has made aluminium an attractive material for powder metallurgy processing. 1 -4 Du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

1987
1987
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(29 citation statements)
references
References 2 publications
0
28
0
1
Order By: Relevance
“…Researchers investigating the sintering mechanisms of aluminium and its alloys tend to agree [2,3,[17][18][19][20][21][22][23][24][25] that successful sintering requires a liquid phase that penetrates the stable, but spalled, aluminium oxide film covering the powder particles. For any aluminium based pre-alloyed powder or elemental powder mixture the appearance of a liquid phase during sintering results from the presence of alloying elements, like Cu, Mg, Zn, Sn, forming low melting point alloys with Al.…”
Section: Local Heating Of the Sintered System Resulting In Higher Lomentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers investigating the sintering mechanisms of aluminium and its alloys tend to agree [2,3,[17][18][19][20][21][22][23][24][25] that successful sintering requires a liquid phase that penetrates the stable, but spalled, aluminium oxide film covering the powder particles. For any aluminium based pre-alloyed powder or elemental powder mixture the appearance of a liquid phase during sintering results from the presence of alloying elements, like Cu, Mg, Zn, Sn, forming low melting point alloys with Al.…”
Section: Local Heating Of the Sintered System Resulting In Higher Lomentioning
confidence: 99%
“…Hence, the surface liquid will promote further disruption of any remaining oxide film. Furthermore, liquid aluminium may penetrate the interface aluminium/alumina and also in this way destroy the oxide film, similarly to that shown for the Al-Cu system [18]. With regard to the greater volume expansion coefficient of the melt than of solid aluminium, this melt can also affect oxide crust degradation as a result of its local expansion.…”
Section: Dsc Mw/mgmentioning
confidence: 95%
“…It is well-known that for an effective liquid phase sintering, a wetting liquid represents an essential requirement. Authors (Kehl & Fischmeister, 1980) suggested that the Al-CuAl 2 eutectic can wet Al 2 O 3 at 873 K. However, not even magnesium additions (to melt aluminium) reduce the contact angle sufficiently to produce wetting (Martín et al, 2004); (Danninger, 1987); (Martín & Castro, 2007). This is possibly the main reason why sintering Al-Zn-Mg-Cu and Al-Mg-Si-Cu-Fe aluminium alloys still cannot be considered that easy.…”
Section: Fig 10 Oxide Layer Covering Aluminium Particlesmentioning
confidence: 99%
“…In particular, the effect of copper in the alloys seems to be efficacious and therefore the sintering behaviour of Al-Zn-MgCu alloys needs to be developed properly. Authors (Kehl & Fischmeister, 1980) suggested that the Al-CuAl 2 eutectic can wet Al 2 O 3 at 873 K. However, magnesium additions to molten aluminium reduce the contact angle sufficiently to produce wetting (Ip et al, 1993); (Liu et al, 1992). The work of adhesion of liquid metals on oxide surfaces increases with the free energy of formation of the metal oxide.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] In order to achieve effective sintering, the surface oxide layer needs to be removed and/or reduced. The previous investigations have shown some effective methods to remove and/or reduced the surface oxide film, for example, the use of liquid phases in the solid-state sintering, 4) mechanical breakdown by friction between surfaces, 5,6) ion beam bombardment treatment in a vacuum chamber, 7,8) the use of active alloying elements such as magnesium (Mg) and lithium (Li), [9][10][11][12] and so on.…”
Section: Introductionmentioning
confidence: 99%